A novel approach for pineapple leaf fiber processing as an ultimate fiber using existing machines - Mohammad, Abdul Jalil; Moniruzzaman, Md.; Parvez, Md. Shohan; Siddika, Ayesha; Abdul Gafur, Md.; Repon, Md. Reazuddin; Hossain, Md. Tanjim (Elsevier Ltd, 2021)
This research aims to study the spinnability of pristine PALF and PALF blended cotton using the existing spinning machines. Apron draft ring spinning frame and flyer jute spinning frame were used to produce 100% PALF yarn and the yarns count were found 121 tex and 138 tex separately. Besides, 90:10 and 80:20 cotton-PALF blended 30 tex yarn spun in a cotton spinning system with different twist factors. With both yarns, two samples; 1/1 plain and 3/1 twill fabrics, were fabricated through equal density. For plain and twill fabric, PALF yarn of 121 tex and 138 tex were used in the warp way, respectively and PALF blended cotton yarn of 60 tex was used in the weft way. Through the study, physio-mechanical properties of the samples were explored and FTIR & XRD patterns were analyzed to perform the task for diversified use as an ultimate fiber in industrial and domestic purposes.